Rooting Studies of Punica granatum and Dalbergia sissoo Cuttings under Controlled Phyto-environment Conditions - Shamet, G. S.; Kumar, S. (Indian Forester, 1988)
Exogenous application of auxins promoted root formation in cuttings taken from one-year old branches of Punica granatum and Dalbergia sissoo under controlled conditions. All the concentrations of IBA, 10,000 and 15,000 mg/l of IAA and 2,000 mg/l of NAA were most effective when applied as quick dip method. Auxins not only enhanced root formation but also increased the number of roots per cutting and average root length.